The control of Foxp3+ regulatory T cell by interleukin-4 receptor alpha-mediated signaling - Mohamed, Abdel Rahman Ahmed Nada (Department of Pathology, 2019)
T regulatory (Treg) cells play a pivotal role in the maintenance of self-tolerance and immune homeostasis. Forkhead box P3 (Foxp3)+ Treg function is controlled by environmental cues of which cytokine-mediated signaling is a dominant component. Recently, Interleukin (IL)-4 has been shown to play an important role in determining the fate of Foxp3+ Tregs. In vivo, IL-4-mediated signaling via Interleukin-4 receptor alpha (IL4Rα) was convincingly shown to mediate Treg transdifferentiation into ex-Foxp3 Th2 or Th17 cells, suggesting a negative regulation of Foxp3+ Tregs by IL-4Rα-mediated signaling. Puzzlingly, however, IL-4-mediated signaling was also independently found to reinforce the Foxp3+ Tregs, counter-arguing for the positive regulation of Foxp3+ Tregs by IL-4Rα-mediated signaling. In the face of such a conundrum, the present work was set forth as an attempt to unambiguously and conclusively decipher the bases of the regulation of Foxp3+ Treg by IL-4Rα-mediated signaling using transgenic murine models. It was first noted that Foxp3+ Treg cells do express IL-4Rα under steady-state. Furthermore, in vitro, purified CD25+ Tregs were prompted to higher Foxp3 expression and increased survival upon stimulation with IL-4 arguing for a potentiating role of IL-4Rα mediated signaling on Foxp3+ Treg cells. To better address the need for the host Foxp3+ Treg cells to express IL-4Rα as observed, we generated Foxp3-specific IL-4Rα deficient mice where IL-4Rα is specifically deleted from Foxp3+ T cells in the whole organism. Even though naïve Foxp3cre IL-4Rα -/lox mice model at homeostasis did neither reveal any significant alteration of the cellular, tissular and phenotypic profile nor development of spontaneous inflammatory disorder when compared to wild-type mice, under S. mansoni infection impairment IL-4Rα-mediated signaling on Foxp3+ Tregs resulted in heightened activation marker expression and elevated T cell effector functions as indicated by increased cytokines production and greater T cell proliferation rate. This heightened immune responsiveness translated overall into an exacerbated parasitic egg-driven fibrogranulomatous inflammation in the liver and the gut of schistosomiasis-diseased Foxp3cre IL-4Rα-/lox mice. Furthermore, in another model of helminth infection with the parasitic nematode, Nippostrongylus brasiliensis, Foxp3cre IL-4Rα-/lox mice showed a higher level of mucus and exaggerated emphysematous pathology in the lungs. Interestingly, the impairment of IL-4Rα signaling within the Foxp3+ Treg population in Foxp3cre IL-4Rα-/lox mice led to a reduced recruitment of Foxp3+ Tregs and a diminished expression of Foxp3, and other associated Treg suppressive markers (i.e. IRF4 and Helios) during the course of these helminth infections. Taken together, our findings supported a role for IL-4Rα signaling in the positive regulation of Foxp3+ Tregs function and thus, the suppression of inflammatory responses during helminth infections. In conclusion, this work demonstrated a positive role for IL-4Rα mediated signaling in the biology of Foxp3+ Treg cells whereby the latter cells require IL-4Rα signaling to survive and maintain Foxp3 expression and suppressive functions so as to efficiently control tissue inflammatory responses during infection. The data presented do provide insights into the mechanisms of Foxp3+ Treg regulation that are highly relevant for the therapeutic control of inflammation during infectious diseases.